Philippians, Colossians and Philemon - MacDonald, William (Oak Park, IL Emmaus Correspondence School, 1972)
Includes bibliographical references.
First published 1960.
Keywords: Bible. N.T. Philippians -- study and teaching; Bible. N.T. Colossians -- study and teaching; Bible. N.T. Philemon -- study and teaching